MODEL KEPEMIMPINAN EFEKTIF - I Gusti Ayu Manuati Dewi Fakultas Ekonomi Universitas Udayana, Denpasar (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2009)
From several decades, research about leadership has been directed toward exploration of informationrelated to determinant of leadership effectiveness. One out of these thousands of researches is done byLocke et al. (2002) which based on their study wrote a book about leadership effectiveness. They thendeveloped a leadership effectiveness model in organizational and business fields through qualitativeapproach. In this model there are four components must be fulfilled by a leader, i.e motive and traits;knowledge, skill, and ability; vision; and implementation of vision. This book provide a comprehensiveperspective about the essence of leadership because its picture deeply and detail related to key componentsof leadership effectiveness. However, they not discuss about leader ability to affect follower at all. Thislimitation may be due to this study has carried out through qualitative approach. Despite this limitation,there is one interesting matter must be observed attentively. Locke et al. points out the importance ofmanagement of meaning must be possessed by a leader, so he/she can manage and define situations as acritical ability that can be used as a guidance of action by the followers.